2012
DOI: 10.1093/humrep/des391
|View full text |Cite
|
Sign up to set email alerts
|

Age at menopause and its influencing factors in a cohort of survivors of childhood cancer: earlier but rarely premature

Abstract: This study provides data on risk factors for a reduced fertility window in order to inform survivors at risk and help oncologists to design new therapeutic protocols avoiding this risk. This study does not confirm the high rate of premature menopause reported by the Childhood Cancer Survivor Study, but this population differs from theirs (no leukemia and a lower percentage of lymphoma).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 22 publications
8
52
1
1
Order By: Relevance
“…Thus, compensatory mechanisms may occur in the remaining ovary . In a study of childhood cancer survivors with mean age of diagnosis of 5 years old, Thomas‐Teinturier and colleagues found that those with unilateral oophorectomy experienced menopause seven years earlier than those without . The more pronounced effect in younger women, seven years versus one year earlier menopause, corroborates well with our results, as women treated with unilateral oophorectomy at younger ages in our study are more likely to enter menopause earlier.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, compensatory mechanisms may occur in the remaining ovary . In a study of childhood cancer survivors with mean age of diagnosis of 5 years old, Thomas‐Teinturier and colleagues found that those with unilateral oophorectomy experienced menopause seven years earlier than those without . The more pronounced effect in younger women, seven years versus one year earlier menopause, corroborates well with our results, as women treated with unilateral oophorectomy at younger ages in our study are more likely to enter menopause earlier.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies suggest that women who receive certain types of chemotherapy such as alkylating agents, those older than 40 years, and those treated with Tamoxifen are more likely to experience amenorrhea and earlier menopause (18, 19). These studies have mostly focused on breast cancer survivors with relatively short follow-up times after cancer diagnosis (median=3.1 years).…”
Section: Introductionmentioning
confidence: 99%
“…There was 1 study which described the effect of radiation therapy in preterm birth [19], the RR of preterm birth was 1.83 (95 % CI was 1.37-2.46). Because of the limitation of the studies, the meta-analysis for these factors could not be proceeded.…”
Section: Resultsmentioning
confidence: 99%